2021
DOI: 10.46483/deuhfed.814994
|View full text |Cite
|
Sign up to set email alerts
|

Salutojenik Model ve Yaşlı Sağlığında Kullanımı

Abstract: Nüfusun yaşlanması dünya çapında bir eğilimdir. İnsanlar artık daha uzun yaşadıkça, sakatlığın önlenmesi, fiziksel fonksiyonların sürdürülmesi, kronik hastalıklardan kaynaklanan komplikasyonların önlenmesi ve yaşanacak yıllar yerine yıllara yaşam katmak daha önemli hale gelmiştir. Tüm bunları sağlamak için yaşlı nüfusun sağlığının geliştirilmesine yönelik yaklaşımlar değer kazanmıştır. Bu kapsamda sağlığının geliştirilmesine yönelik geliştirilen birçok model yaşlı bireylerde de kullanılmıştır. Özellikle son ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
1
0
1
Order By: Relevance
“…However, men do not participate in family planning adequately due to the social status difference between women and men. 21,22 Recent studies have found that men's lack of knowledge and understanding increases the stigma related to family planning and the perception that men want more children increases the possibility for women to become a secret user of family planning. 23,24 In countries, especially like Turkiye where a patriarchal and traditional structure exists, knowledge and attitudes of young people related to family planning methods are noteworthy.…”
Section: Introductionmentioning
confidence: 99%
“…However, men do not participate in family planning adequately due to the social status difference between women and men. 21,22 Recent studies have found that men's lack of knowledge and understanding increases the stigma related to family planning and the perception that men want more children increases the possibility for women to become a secret user of family planning. 23,24 In countries, especially like Turkiye where a patriarchal and traditional structure exists, knowledge and attitudes of young people related to family planning methods are noteworthy.…”
Section: Introductionmentioning
confidence: 99%
“…Konular probleme göre ilişkilendirilerek bilginin entegrasyonunu gerektirir. Buda öğrencinin YBÖ yeteneğinin gelişmesini sağlamaktadır (Dereli, Yıldırım Sarı ve Tokem, 2021;Uysal Toraman, Bayık Temel, Kalkım ve Erkin Balyacı, 2013).…”
Section: Introductionunclassified